Social media jurors: conceptualizing and analyzing online public engagement in reference to legal cases - Grossman, Nerit (Crime, law and social change, 2023)
Jurors are people who are exposed to legal proceedings and consequently exercise their judgment. A broad literature on law and film discusses the analogy between formal jurors, who are assigned to jury duty by the legal system, and "informal jurors"- "viewers-as-jurors" who encounter the legal system indirectly, through the media. In this paper, we identify a new category of "informal jurors", which refers to public discourse and actions concentrated on social media arenas in reference to legal cases. We argue that this category, which we call "social media jurors", maintains a tight correspondence with existing categories of jurors, but is distinguished from them by their extended abilities for speech and action. This article is based on a netnographic study, by which we illustrate our argument through the online activity in support of Roman Zadorov. Zadorov was convicted of murdering a young girl in Israel, while a large majority of Israelis continue to support his innocence and carry out extensive action on social media in support of this cause.